Late booking at the Michael Mapongwana antenatal clinic, Khayelitsha : understanding the reasons - De Vaal, Sybrand Johannes (Stellenbosch : University of Stellenbosch, 2014)
Thesis (MMed)--Stellenbosch University, 2011.